Peran mediasi financial stress dalam hubungan antara financial self-efficacy dan purchase decision making pada generasi Z - Achmad Nur Wahyu Kartiko; Nasywa Ummi Syarifah; Windijarto Windijarto (Journal of Management and Digital Business, 2026)
This study examines the role of financial stress as a mediator in the relationship between financial self-efficacy and purchase decision making among generation Z in Indonesia. Using validated psychometric instruments and bootstrap mediation analysis, the findings reveal full mediation by financial stress with a statistically significant indirect effect. Contrary to conventional theoretical predictions, financial self-efficacy is strongly and positively associated with financial stress. In contrast, financial stress shows a significant negative predictive relationship with the quality of purchase decision-making. The direct path between financial self-efficacy and purchase decision making was not statistically significant. These empirical findings suggest that high financial self-efficacy may paradoxically increase psychological burden and performance expectations in Indonesia’s digital era, thereby intensifying stress levels that undermine cognitive decision-making. This study contributes novel insights into counterintuitive psychological mechanisms that underlie financial behavior in the context of Indonesia’s digital transformation, highlighting the importance of integrating stress management into financial education programs targeting generation Z.